Enhanced Glutamate Synthesis and Export by the Thermotolerant Emerging Industrial Workhorse Bacillus methanolicus in Response to High Osmolarity - Frank, Christine; Hoffmann, Tamara; Zelder, Oskar; Felle, Max F.; Bremer, Erhard (Frontiers in Microbiology, 2021)
The thermotolerant methylotroph Bacillus methanolicus MGA3 was originally isolated from freshwater marsh soil. Due to its ability to use methanol as sole carbon and energy source, B. methanolicus is increasingly explored as a cell factory for the production of amino acids, fine chemicals, and proteins of biotechnological interest. During high cell density fermentation in industrial settings with the membrane-permeable methanol as the feed, the excretion of low molecular weight products synthesized from it will increase the osmotic pressure of the medium. This in turn will impair cell growth and productivity of the overall biotechnological production process. With this in mind, we have analyzed the core of the physiological adjustment process of B. methanolicus MGA3 to sustained high osmolarity surroundings. Through growth assays, we found that B. methanolicus MGA3 possesses only a restricted ability to cope with sustained osmotic stress. This finding is consistent with the ecophysiological conditions in the habitat from which it was originally isolated. None of the externally provided compatible solutes and proline-containing peptides affording osmostress protection for Bacillus subtilis were able to stimulate growth of B. methanolicus MGA3 at high salinity. B. methanolicus MGA3 synthesized the moderately effective compatible solute L-glutamate in a pattern such that the cellular pool increased concomitantly with increases in the external osmolarity. Counterintuitively, a large portion of the newly synthesized L-glutamate was excreted. The expression of the genes (gltAB; gltA2) for two L-glutamate synthases were up-regulated in response to high salinity along with that of the gltC regulatory gene. Such a regulatory pattern of the system(s) for L-glutamate synthesis in Bacilli is new. Our findings might thus be generally relevant to understand the production of the osmostress protectant L-glutamate by those Bacilli that exclusively rely on this compatible solute for their physiological adjustment to high osmolarity surroundings.